2008
DOI: 10.1111/j.1530-0277.2007.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Ethanol Intoxication on Salivary Proteins of Innate and Adaptive Immunity

Abstract: Our report is the first to show that acute ingestion of relatively large, yet tolerable dose of alcohol, significantly disturbs salivary antimicrobial defense system. Reduced lysozyme level and decreased peroxidase activity may contribute to increased susceptibility to infections, when acute alcohol intake coincides with exposure to pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 54 publications
0
51
0
Order By: Relevance
“…It has been reported that there is a reduction in the stimulated release of lactoferrin after acute in vitro effect of ethanol on neutrophils [22], a tendency towards an increase in serum lactoferrin concentration in alcohol dependent patients [14], and no effect of acute alcohol intoxication on salivary lactoferrin concentration [7]. The objective of the present study was to determine for the first time the effect of chronic alcohol consumption on the concentration and output of salivary lactoferrin.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that there is a reduction in the stimulated release of lactoferrin after acute in vitro effect of ethanol on neutrophils [22], a tendency towards an increase in serum lactoferrin concentration in alcohol dependent patients [14], and no effect of acute alcohol intoxication on salivary lactoferrin concentration [7]. The objective of the present study was to determine for the first time the effect of chronic alcohol consumption on the concentration and output of salivary lactoferrin.…”
Section: Introductionmentioning
confidence: 99%
“…Following the World Health Organization criteria, the level of dental caries in subjects was determined using the DMFT index (decayed, missing or filled teeth; [7]). Gingival status was assessed using the gingival index (GI; Löe and Silness [23]) and papilla bleeding index (PBI; [24]).…”
Section: Data and Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations